If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -5(-1x + -4) = 2 Reorder the terms: -3x + -5(-4 + -1x) = 2 -3x + (-4 * -5 + -1x * -5) = 2 -3x + (20 + 5x) = 2 Reorder the terms: 20 + -3x + 5x = 2 Combine like terms: -3x + 5x = 2x 20 + 2x = 2 Solving 20 + 2x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 2x = 2 + -20 Combine like terms: 20 + -20 = 0 0 + 2x = 2 + -20 2x = 2 + -20 Combine like terms: 2 + -20 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| -5(y+2)=10 | | -1-7x+6x=-1 | | 4x+6y=103x+7y=12.5 | | 6(7x-1)=42x-6 | | 5(x+2)=-7x | | sqrt(-6y+37)=y-5 | | z=20x+6y | | 4y+9=z | | 3n-5=3n | | (3x^2-20x-7)=0 | | -3x-4x-6=-61 | | sin(x)=0.8191 | | 37=-7x+2(5x+2) | | 3log(4x)2=10 | | x^4+x^3+4x^2-24x-72=0factor | | x^4+x^3+4x^2-24x-72=0 | | factorx^4+x^3+4x^2-24x-72=0 | | 3(2x+5)+14=4(3x-7)-3 | | 7x=41 | | 6h-34=-6+h+14 | | -3w-4(-3x+3w)-6x= | | 4(-3)+9=-3 | | 2(x+4)+x=26 | | e^3x=e^7x-2 | | X^3=25.12 | | -54+97+(-10)+35= | | 3(5-u)= | | 3t+.17=t-3 | | 3(-u)= | | (6+8x)+(7x+10)=180 | | 7(x-6)=4x-39 | | -17a-3b+c=-16 |